Hubungan Pengetahuan Ibu Hamil tentang HIV dengan Minat Untuk Periksa HIV (PMTCT): Relationship between knowledge of pregnant women about HIV and interest in HIV testing (PMTCT) - Wardhani, Ratih Kusuma; Dinastiti, Vide Bahtera; Azizah, Eva Nur (Universitas Muhammadiyah Sidoarjo, 2019)
This is due to the discovery of potent and safe vaccines against HIV infection and AIDS. The purpose of this study to determine the relationship of knowledge about HIV pregnant women with an interest to check HIV (PMTCT) in Health Center Gurah Kediri district. The research design used was cross sectional. The research site was conducted at Gurah Community Health Center, Gurah District, Kediri Regency and conducted in May - June 2017. The research samples were 30 respondents. It used Purposive sampling. The independent variable in this study is the knowledge of pregnant women about HIV. The dependent variable in this study is the interest of pregnant women to check for HIV. The instrument in this study used a questionnaire. The data analysys method was Spearman Rank by using SPSS. Knowledge of pregnant women about HIV most 17 respondents (56.7%) and a fraction less 5 respondents (16.7%) enough. Interest of the respondent to check HIV (PMTCT) do not interest most of 13 respondents (43.3%) and a small 8 respondents (26.7%) less interest. There is a relationship between knowledge of HIV pregnant women with an interest to check HIV (PMTCT) with Spearman Rank analysis value is 0.645 with a positive figure shows a strong relationship level. Knowledge greatly affect the interest in performing HIV (PMTCT). Pregnant women are expected to increase the knowledge by attending counseling given by health workers, especially tentag HIV so that it will increase the interest to check HIV (PMTCT).